2014
DOI: 10.1038/ncomms6506
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the hexameric HerA ATPase reveals a mechanism of translocation-coupled DNA-end processing in archaea

Abstract: The HerA ATPase cooperates with the NurA nuclease and the Mre11-Rad50 complex for the repair of double-strand DNA breaks in thermophilic archaea. Here we extend our structural knowledge of this minimal end-resection apparatus by presenting the first crystal structure of hexameric HerA. The full-length structure visualises at atomic resolution the N-terminal HerA-ATP Synthase (HAS) domain and a conserved C-terminal extension, which acts as a physical brace between adjacent protomers. The brace also interacts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
63
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 58 publications
(129 reference statements)
5
63
0
Order By: Relevance
“…DrHerA alone (67.4 kDa per protomer) eluted at around 10 ml on Superdex 200 as hexamers (Fig. 3C), consistent with earlier reports for M. thermoautotrophicus (17) and S. solfataricus (43) and the SsoHerA structure (53,54). DrNurA (38.3 kDa per protomer) alone eluted around 14 ml on Superdex 200, indicating a monomer-dimer equilibrium (Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…DrHerA alone (67.4 kDa per protomer) eluted at around 10 ml on Superdex 200 as hexamers (Fig. 3C), consistent with earlier reports for M. thermoautotrophicus (17) and S. solfataricus (43) and the SsoHerA structure (53,54). DrNurA (38.3 kDa per protomer) alone eluted around 14 ml on Superdex 200, indicating a monomer-dimer equilibrium (Fig.…”
Section: Resultssupporting
confidence: 78%
“…A previous S. solfataricus study showed that HerA and NurA interacted with a 6:2 stoichiometry (43), consistent with the crystal structure of the NurA-HerA complex (53,54). We purified DrHerA and DrNurA separately for analysis by gel filtration chromatography (see Fig.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations